Educação ambiental e gestão de recursos hídricos: a Bacia Hidrográfica da Estrada Nova, Belém/PA - RIOS, Naiara de Almeida (Universidade Federal do Pará, 2019)
The Estrada Nova Hydrographic Basin has been receiving, since 2009, urban and environmental infrastructure works, from the implementation of the Estrada Nova Sanitation Program, PROMABEN. Inserted in this program, environmental education ap-663pears as a management tool that assists in the transformation of the relationship between human beings and nature. And it is thinking about the importance of environmental education in the management process, especially in water resources, that this study intends to evaluate the influence of the environmental education actions developed by PROMABEN in the Estrada Nova Hydrographic Basin, Belém / PA. To that end, the perception of the residents and schools of the neighborhoods of the basin was analyzed, and an Environmental Education Indicator was created for the area. For the development of the research, there were on-site visits and interviews with residents of the area, with teachers and school technicians, and a representative of PROMABEN. The qualitative-quantitative method was used for the analysis of results, and the Factorial Analysis technique for the creation of the Environmental Education Indicator. The results demonstrate that PROMABEN has not developed environmental education in the Estrada Nova Hydrographic Basin and is therefore inconclusive as to the execution and finalization of its objectives and results, which compromises the role of environmental education in the management process. Thus characterizing, on the one hand, the accumulation of certain actions and on the other, incomplete results that need to be evaluated, and validated or not, by the municipal public power. Based on this study, it is hoped to contribute to the deepening of discussions on public policies, environmental management, and, above all, the need to develop environmental education in programs such as PROMABEN, especially in the city of Belém. an instrument of change of social values that prepares subjects for citizenship from a new world view, where water resources, as well as the other natural elements, are inherently thought of human beings.